(untitled) - Brooks, Myrna LaFleur (St. Louis ( Missouri ), 2003)
This books offers the only comprehensive, in-depth coverage available on health unit coordinating. From greeting new patients to dealing with visitors, transcribing physicians' orders for patient treatment, maintaining statistical reports, preparing patient charts, and more... each chapter provides theory discussion of key topics.
Keywords: Hospital ward clerks,Medical records,Medicine; Terminology